Health and well-being tourism: analysis of motivational factors through spa experiences - Ferreira, Jéssica (2024)
The increase concern about health and disease prevention and the average life expectancy increase, in developed countries, are factors that have played an important role in changing the tourist demand for health and wellness destinations segments of great importance, with a significant impact on the economy and employment in the regions (Ministry of Economy, 2021). Thus, the objective of this work is to study the motivations of tourists who seek thermal spaces, so that the managers of thermal organizations are able to respond to the new demands of the market. Based on the knowledge of the different motivations, spa organizations will be able to adjust their offer to the demand needs.